Penerapan Decision Trees dalam Mendeteksi Pola Tidur Sehat Berdasarkan Kebiasaan Gaya Hidup - Imam Nawawi; Zaehol Fatah (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2024)
A good sleep pattern is very important for our body's health both physically and mentally, while lifestyle habits such as physical activity and diet play a big role in influencing sleep quality. By using a decision tree, researchers aim to predict whether we have a healthy sleep pattern or not based on lifestyle. Healthy sleep patterns are regular and quality sleep habits to maintain our physical health. Healthy sleep patterns generally involve sleeping 8 hours – 9 hours per night, having a regular and consistent sleep time. The decision tree model was chosen because of the decision tree's ability to provide accurate predictions and produce rules that are easy to understand. This model can help us raise awareness of the importance of a healthy lifestyle in maintaining sleep quality.